Practical responses to confidentiality dilemmas in elite sport medicine - Malcolm, D.; Scott, A. (British Journal of Sports Medicine, 2014)
Aim: To examine the ethical challenges of upholding patient confidentiality in sports medicine and the practical responses of clinicians to these challenges.